Leveraging Cell‐Free Supernatants of Phyllospheric Bacteria to Combat Wheat Pathogens and Boost Growth - Saleem, Noshaba; Badar, Ayesha; Aqueel, Rhea; Ijaz, Umer Zeeshan; Malik, Kauser Abdulla (Plant-environment interactions (Hoboken, N.J. : 2018), 2025)
ABSTRACT Wheat is a major staple crop in Pakistan but faces significant threats from biotic stressors such as powdery mildew (Blumeria graminis) and stripe rust (Puccinia striiformis). These fungal diseases can drastically reduce wheat yields, leading to substantial economic losses. This study aimed to evaluate the antifungal efficacy of Cell Free Supernatants (CFSs) from Serratia marcescens and Fictibacillus spp. (both originally derived from phyllosphere of Gossypium arboreum) against these fungal pathogens and assess their impact on wheat growth and yield. Wheat plants (Triticum aestivum, Galaxy‐2013) were treated with CFSs from both strains, alongside control groups treated with Salicylic Acid (SA), Gibberellic Acid (GA3), and water (negative control). Disease severity was assessed using leaf area and spore count assays. Plant growth parameters, including height, fresh and dry weight, grain count, and spike number, were measured. Metabolomic analysis of the CFSs was conducted using 1H NMR. CFS treatments significantly reduced disease severity, with the lowest average percentage disease (APD) observed in the Serratia marcescens group for stripe rust (1.86%) and in the GA3 group for powdery mildew (1.30%). Fictibacillus spp. CFS also reduced the severity of both pathogens. CFS from Serratia marcescens resulted in the highest grain count and biomass. NMR analysis revealed the presence of antifungal and growth‐promoting compounds in the CFSs. CFSs from Serratia marcescens and Fictibacillus spp. show promise as effective bio‐stimulants and biocontrol agents against fungal diseases in wheat, offering a sustainable alternative to chemical treatments. Their application could improve wheat yield and contribute to more sustainable agricultural practices.